Immune reconstitution inflammatory syndrome after hematopoietic stem cell transplantation in a FOXN1-deficient patient - Çorbalı, Osman; Gemici Karaaslan, Hatice Betül; Aydemir, Sezin; Önal, Pınar; Kendir Demirkol, Yasemin; Nepesov, Serdar; Kıykım, Ayça; Çokuğraş, Haluk (Lippincott Williams and Wilkins, 2023)
The FOXN1 gene mutation is a unique disorder that causes the nude severe combined immunodeficiency phenotype. In patients with severe combined immunodeficiency, hematopoietic stem cell transplantation (HSCT) is life-saving if performed earlier. Thymic transplantation is the curative treatment for FOXN1 deficiency because the main pathology is thymic stromal changes. In this report, we describe the clinical features of a Turkish patient with a homozygous FOXN1 mutation treated with HSCT from his human leukocyte antigen-matched sibling. On follow-up, he showed Bacille Calmette Guerin adenitis and was evaluated as having immune reconstitution inflammatory syndrome. By presenting our patient, we aimed to draw attention to the development of HSCT and subsequent immune reconstitution inflammatory syndrome as a treatment option in patients with FOXN1 deficiency.
Keywords: FOXN1; Nude SCID; SCID; HSCT; IRIS